2017
DOI: 10.1002/ecs2.1736
|View full text |Cite
|
Sign up to set email alerts
|

Landscape diversity and crop vigor outweigh influence of local diversification on biological control of a vineyard pest

Abstract: The influence of local and landscape habitat diversification on biological control of the Western grape leafhopper (Erythroneura elegantula Osborn) by its key parasitoids Anagrus erythroneurae S. Trjapitzin & Chiappini and Anagrus daanei Triapitsyn was studied in wine grape vineyards. At the landscape scale, Anagrus rely on alternative host species in non‐crop habitats outside of the vineyard to successfully overwinter, while at the local scale vineyard diversification can provide resources, such as shelter an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(32 citation statements)
references
References 95 publications
3
28
1
Order By: Relevance
“…Our results are in accordance with Costello and Daane () and Wilson et al. (, ), who reported similar associations of lowered leafhopper densities on vines with lowered leaf nitrogen.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…Our results are in accordance with Costello and Daane () and Wilson et al. (, ), who reported similar associations of lowered leafhopper densities on vines with lowered leaf nitrogen.…”
Section: Discussionsupporting
confidence: 93%
“…Numbers of spiders also increased slightly—but significantly—on vines in the non‐irrigated native grass treatment. Studies using exotic plant species as ground covers also reported increases in generalist predator numbers (Nicholls et al., ; Wilson et al., ). Spiders are sensitive to habitat structure and the grasses tested may have provided additional structure that benefited spiders and translated into higher numbers on vines.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations